2020
DOI: 10.1039/d0bm00805b
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo studies on ultrafine-grained biodegradable pure Mg, Mg–Ca alloy and Mg–Sr alloy processed by high-pressure torsion

Abstract: High-pressure torsion (HPT) can refine the microstructure and consequently modify the properties, such as mechanical and corrosion properties, of Mg and its alloys. Biodegradable magnesium materials alloyed with the essential...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 82 publications
1
24
0
Order By: Relevance
“…The detailed pre-clinical studies of these alloys were summarized in Table 1. [52] pin Rat femoral bones 7 days 0.15 ± 0.03 mm/y 26 Mg enriched (>99 wt.%) [53] pin Rat femoral bones 4, 24, 52 weeks 16 ± 5 µm/y Pure Mg high pressure (99.98 Mg in wt.%) [54] disk Rat femoral bones 24 weeks 0.41 ± 0.02 mm/y WE43 (>92.0 Mg in wt.%) [55] plates and screw Dogs-LeFort I osteotomy 4, 12, and 24 weeks NA 1 WE43 (>92.0 Mg in wt.%) [56] screw Rabbit tibiae 4, 8, 12 and 16 weeks NA 1 WE43 (>92.0 Mg in wt.%) [57] pin Rat tibiae 52 weeks NA 1 WE43/WE43T5 (>92.0 Mg in wt.%) [58] screw Sheep mandibule 6 and 24 weeks NA 1 MgYREZr (>92.0 Mg in wt.%) [59] screw Rabbit femoral bones 1, 12, and 52 weeks NA 1 JDBM (>95.0 Mg in wt.%) [60] screw Rabbit mandible bones 1, 4, and 7 months 0.161 ± 0.025 mm/y (1 month), 00.218 ± 0.030 mm/y (7 months) NZK (>96.0 Mg in wt.%) [61] rod Rabbit femoral bones 28 and 56 days 0.66 mm/y (28 days) and 0.48 mm/y (56 days) Mg-Zn (94.0 Mg in wt.%) [62] rod Rabbit femoral bones 14 weeks 2.32 mm/y ZX00 (>99.0 Mg in wt.%) [63] pin Rat femoral bones and sheep tibiae 6, 12 and 24weeks 0.08 mm/y (rat) and 0.045 mm/y (sheep) ZX00 (>99.0 Mg in wt.%) [64] screw Sheep tibiae 3, 6 and 12 weeks NA 1…”
Section: Mg and Its Alloysmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed pre-clinical studies of these alloys were summarized in Table 1. [52] pin Rat femoral bones 7 days 0.15 ± 0.03 mm/y 26 Mg enriched (>99 wt.%) [53] pin Rat femoral bones 4, 24, 52 weeks 16 ± 5 µm/y Pure Mg high pressure (99.98 Mg in wt.%) [54] disk Rat femoral bones 24 weeks 0.41 ± 0.02 mm/y WE43 (>92.0 Mg in wt.%) [55] plates and screw Dogs-LeFort I osteotomy 4, 12, and 24 weeks NA 1 WE43 (>92.0 Mg in wt.%) [56] screw Rabbit tibiae 4, 8, 12 and 16 weeks NA 1 WE43 (>92.0 Mg in wt.%) [57] pin Rat tibiae 52 weeks NA 1 WE43/WE43T5 (>92.0 Mg in wt.%) [58] screw Sheep mandibule 6 and 24 weeks NA 1 MgYREZr (>92.0 Mg in wt.%) [59] screw Rabbit femoral bones 1, 12, and 52 weeks NA 1 JDBM (>95.0 Mg in wt.%) [60] screw Rabbit mandible bones 1, 4, and 7 months 0.161 ± 0.025 mm/y (1 month), 00.218 ± 0.030 mm/y (7 months) NZK (>96.0 Mg in wt.%) [61] rod Rabbit femoral bones 28 and 56 days 0.66 mm/y (28 days) and 0.48 mm/y (56 days) Mg-Zn (94.0 Mg in wt.%) [62] rod Rabbit femoral bones 14 weeks 2.32 mm/y ZX00 (>99.0 Mg in wt.%) [63] pin Rat femoral bones and sheep tibiae 6, 12 and 24weeks 0.08 mm/y (rat) and 0.045 mm/y (sheep) ZX00 (>99.0 Mg in wt.%) [64] screw Sheep tibiae 3, 6 and 12 weeks NA 1…”
Section: Mg and Its Alloysmentioning
confidence: 99%
“…This rate varies depending on the type of alloys and the type of animal model. For rats, the small animal model is widely used, it varies from 0.41 to 0.40 mm/year for pure Mg [ 52 , 54 ] and 0.08 mm/year for ZX00 [ 63 ].…”
Section: Mg and Its Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…The finer grains produced by SPD are associated with improved mechanical strength [22,23] and recent papers have shown that exceptional ductility is observed in ultrafine grained pure magnesium [24,25]. On top of the improvements in mechanical properties, it has been proved that rolling, equal-channel angular pressing (ECAP) [26], and high pressure torsion (HPT) [27] processing do not compromise biocompatibility and may improve corrosion resistance [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Although the results reported in the literature show that HPT processing displays extraordinary potential to improve the performance of magnesium for biodegradable applications, some sample size issues remain as a concern as it can impact the materials' response in some tests. For example, most of the data on mechanical strength of samples of magnesium processed by HPT were collected from microhardness tests [31,32] or tensile tests in miniature samples [25,30] in which the loading direction is usually parallel to the disc rotation direction. This can impact the results since it is known that the mechanical behavior of magnesium is anisotropic and strength and ductility depends on sample direction [33,34].…”
Section: Introductionmentioning
confidence: 99%